Long Poetry Tradition and Restoration - B, Umarani (Indian Journal of Tamil, 2020)
In each period, poetry has undergone a change in its own structure of structure and its structure of meaning. This change is also seen in the history of long poetry. This change has taken place in terms of subject matter and format. But as a continuation of the tradition, the form of the long poem acquires a new form of free will.